Distribution and seasonal abundance of large cetaceans in the Durban whaling grounds off KwaZulu-Natal, South Africa, 1972–1975. Issue 2 (19th August 2016) - Findlay, KP; Best, PB
Abstract : Daily charts of the aerial search effort (432 206 nautical miles) of the Union Whaling Company and 1 099 sightings of 10 497 whales were available from 628 flights off Durban between 1972 and 1975. Densities of whales were analysed by month and water depth distribution over the four-year period. Low observed densities of blue Balaenoptera musculus, right Eubalaena australis, sei B. borealis and humpback Megaptera novaeangliae whales most likely resulted from earlier whaling pressure. Seasonality of blue, sei and humpback whales was bimodal, indicative of winter migrations to the north of the Durban whaling grounds, whereas the unimodal seasonality of fin whales B. physalus and minke whales B. bonaerensis or B. acutorostrata suggest the offshore region as the northern terminus of their migrations. Sperm whales Physeter macrocephalus migrate northwards offshore of the KwaZulu-Natal coast in autumn/early winter and southwards in late winter/spring, with larger males migrating later than the smaller males and females. Killer whale Orcinus orca presence was coincident with that of offshore minke whales and the southward migrations of other baleen whales, whereas densities of animals deemed as bottlenose whale Hyperoodon planifrons suggest strong early and late summer seasonal abundance in the offshore region. Such extensive surveys offshore of the KwaZulu-Natal coast are unlikely to be repeated; hence, data-extraction of whaling records provides a valuable source of seasonal and distributional information for marine management.